Facial Expressions According to Tones on Jegog Leaf Blade as A Source of Installation Art Works Creation - Indrawan, I Ketut Deni; Mustika, I Ketut; Pemayun, Tjokorda Udiana Nindhia (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2023)
Gamelan Jegog comes from the Jembrana area, where this Jegog has a very melodious and loud voice so that Jegog is well known throughout foreign countries. Gamelan Jegog is made of bamboo. Incidentally, in the Jembrana area there are many bamboo trees and the bamboo grows well because of the fertile soil, many bamboo trees grow and develop there, and that is what prompted Jembrana artists to create musical instruments made of bamboo. The tone in the Jegog gamelan can make a musical rhythm so alive. Each music must have its own rhythm. Tone is a musical movement that is controlled in time. Without good tunes, it's easy to get lost in the music and get out of sync. In Gamelan Jegog there are various melodies and rhythms such as the high and low of a note to make the rhythm of the music being played calm and peaceful. Based on the description above, the tones and facial expressions in Jegog gamelan are the inspiration for creating installation art works. Thus facial expressions according to tone in Gamelan Jegog serve as a source of inspiration in the creation of works as well as being the title for facial expressions according to tone on jegog leaf blades as a source for creating installation art works